TANGGAPAN GURU SEKOLAH DASAR TERHADAP FENOMENA BULLYING DI KALANGAN SISWA - Munifa Sahla Adhitia; Jennyta Caturiasari; Nasya Putry Kusumah; Salsa Amelia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the reactions of elementary school teachers to bullying problems that occur among students. The bullying analyzed includes aggressive behavior that is physical, verbal, and social, which has a negative impact on the mental health of the victims. This study applies a descriptive qualitative method with data collection using an online survey filled out by seven elementary school teachers. The finding of this study indicate that all teachers play an active role in overcoming bullying incidents through various approaches such as sanctions, counselling, open communication with students, and cooperation with parents. Most teachers prefer educational and character development methods over severe punishment. This study emphasize the importance of the role of teachers in preventing and overcoming bullying, including the need for adequate training for teachers to be able to identify signs of bullying and take appropriate intervention actions. These findings are expected to contribute to creating a safe, comfortable school atmosphere that supports student’s maximum growth.